Cross-referencing French hematology teams’ knowledge and perception of end-of-life situations: a national mixed-methods survey - Chloé Prod’homme; Côme Bommier; Laurène Fenwarth; Stephane Moreau; Alice Polomeni (BMC Palliative Care)
Abstract Introduction Haematology is a speciality frequently confronted with end-of-life situations, and teams will be concerned by the question of medical assistance in dying. The Ethics Commission of the French Society of Haematology has conducted a survey on the knowledge and perceptions of healthcare professionals regarding complex end-of-life situations. Methods A cross-sectionalonline survey of hematology professionals in France. The comprehensive online questionnaire addressed respondents’ experience of complex end-of-life situations in hematology, based on 7 clinical vignettes. The survey contained 55 questions, 6 of which were open-ended. They were asked to give their opinion on whether it should be legalized. Justifications were then requested and analyzed by theme. Results The survey was distributed to associations of hematology healthcare professionals (approximately 1,300 members). Overall, 182 healthcare professionals replied, including a third nurses and a third physicians. The average score for identifying complex situations was 7.1 out of 10 (IQR 5.7,8.6), with lesser knowledge of situations involving double effect, euthanasia and sedation for distress than of situations involving limiting or stopping treatment. Training in palliative care was the main driver of knowledge (p = 0.004), as well as being a physician (p < 0.001). We found that the opinions of healthcare professionals regarding the legalization of medical assistance in dying in France were diverse and well-founded. Conclusion Hematology healthcare professionals had lesser knowledge of situations involving double effect, euthanasia and sedation for distress. Knowledge of specific situations impacts professionals’ opinion on legalization of medical assistance in dying.